Stress in Wichí (Mataguayan) and its Interaction with the Word Formation Processes - Nercesian, Verónica (2011)
This paper presents the results of a phonological study of primary stress in Wichí, a Mataguayan language spoken in the Gran Chaco. In addition, it analyzes some word formation processes where morphological information conditions the assignment of stress. The Wichí rhythmic pattern consists of parsing the word into binary iambic feet from left to right. The lengthening of vowels occurs to enforce the optimal structure of the iambic foot. Primary stress is applied to the head of the rightmost foot in the phonological word. The same stress pattern is applied to base words (monomorphemic), words with affixes and/or clitics, and compounds. However, the addition of a group of extrametrical suffixes (locative/directional) and the word formation process by noun incorporation determine the stress assignment and the metrical pattern. In one case, the extrametrical suffixes are not counted in metrical parsing, and as a consequence, they are unstressed. This results in a word with the stress on the penultimate syllable. In the other case, the noun incorporation process is linked to a specific prosodic structure that consists of two unbounded feet, and a stress-stem type rule. This structure facilitates the perception of the morphosyntactic edges.